2020
DOI: 10.18632/aging.103385
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of common and diverged circulating miRNAs between arterial and venous during aging

Abstract: Circulating miRNAs have received extensive attention as non-invasive biomarkers for prediction and diagnosis of disease. However, most samples have been obtained from peripheral venous blood. To evaluate whether peripheral venous miRNAs represent circulating miRNAs from all blood vessels under a given condition, such as aging, we compared the miRNA profiles of venous and arterial plasma between young and aged rats by Illumina next-generation sequencing. The DEseq2 tool was used to obtain differentially-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Different aspects can be used to provide an even more comprehensive systemic picture of miRNAs and aging. First, the cell free part of the blood is also correlated to miRNA aging 44 , 45 . One important aspect are vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Different aspects can be used to provide an even more comprehensive systemic picture of miRNAs and aging. First, the cell free part of the blood is also correlated to miRNA aging 44 , 45 . One important aspect are vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Their extraction can be biased across samples and studies resulting from different extraction chemistries ( Tan et al, 2015 ; Parker et al, 2021 ). The comparison of miRNA stability across different cohorts can be hampered by various physiological parameters impairing their abundance such as subject’s age ( Noren Hooten et al, 2013 ; Ameling et al, 2015 ; Fehlmann et al, 2020 ; Maffioletti et al, 2020 ; Wang et al, 2020 ), gender ( Duttagupta et al, 2011 ; Ameling et al, 2015 ), pregnancy ( Tay et al, 2017 ) or ethnicity ( Patel et al, 2019 ). Moreover, levels of circulating miRNAs can be impacted by alcohol consumption ( Ignacio et al, 2015 ), dietary habit ( Tarallo et al, 2014 ; Liu et al, 2020 ), poor sleep quality ( Baek et al, 2021 ), obesity parameters (body mass index ( Ameling et al, 2015 ), levels of visceral and subcutaneous adipose tissue, or body-fat percentage ( Munetsuna et al, 2018 )), settlement ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…miRNA analysis has also been conducted to explore the influence of aging. Transcriptome analysis of miRNA from the peripheral blood of young and aged rats showed that miR-136-3p and miR-503-3p are differentially expressed with aging and are regulated by NF-κB and SIRT1 [ 95 ].…”
Section: Omics 1 Transcriptome Regulation Of Nf-κb and Agingmentioning
confidence: 99%